The Influence of Store Atmosphere and Bonus Pack on Impulse Buying with Positive Emotion as a Mediating Variable Among Guardian Consumers in Bengkulu City - Konteza, Orecke Aulia; Salim, Muhartini (JURNAL MANAJEMEN MOTIVASI, 2025)
This study examines the effects of store atmosphere and bonus packs on impulse buying and positive emotion, as well as the mediating role of positive emotion among Guardian consumers in Bengkulu. A quantitative method with purposive sampling was applied to 170 respondents. Data were analyzed using SEM-PLS version 4. Results show store atmosphere significantly affects impulse buying, but bonus packs do not. Both variables significantly affect positive emotion, which also significantly mediates the relationship between store atmosphere, bonus packs, and impulse buying.